Pengenalan Akuntansi sebagai Bahasa Bisnis di SMKN 2 Kelompok Teknologi dan Rekayasa Meulaboh - Soufyan, Dara Angreka; Nugroho, Yoga; Agustia, Devi; Maifianti, Khori Suci; Ringo, Liston Siringo (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
Entrepreneurship is a trait that can be cultivated through social roles and experiences, reflecting the inherent entrepreneurial characteristics in individuals and fosters innovation. In Indonesia, vocational education aims to develop skilled human resources at the secondary education level (UU No. 20 of 2003). Vocational schools (SMK) are intended to produce productive, creative, and independent individuals who can efficiently utilize available resources. Aceh Barat Regency ranks tenth out of 23 regencies in Aceh Province in educational success, measured by the Human Development Index (HDI). Despite this, poverty remains above 20%. SMKs can potentially increase HDI and reduce poverty by equipping students with specific skills. The creative outputs of SMK students can form the basis of small industries in West Aceh. Therefore, it is crucial to motivate and invest in vocational education to foster young entrepreneurs. To become entrepreneurs, students need to understand business language, particularly accounting. Vocational education should integrate basic business skills such as accounting, especially in engineering fields, to prepare students for entrepreneurship. This community service activity was conducted at SMK Negeri 2 majoring Engineering and Technology Meulaboh. The activities help students understand entrepreneurship and the importance of accounting as the language of business, equipping them to start businesses based on their school projects. The results indicated that students understood the relationship between accounting and entrepreneurship. The collaboration between the school, lecturers, and students created potential for sustainable activities to prepare future entrepreneurs. Continuous investment in vocational education is essential for developing entrepreneurial skills and reducing poverty in Kabupaten Aceh Barat.